DISCOURSE PATTERNS OF APPLIED LINGUISTICS RESEARCH ARTICLE ABSTRACTS IN ENGLISH - Kamalatul Hafidzoh; Tofan Dwi Hardjanto (English Language and Literature International Conference (ELLiC) Proceedings, 2019)
An abstract has important role in summarizing and promoting its research article. Because of the important role, abstracts contain discourse patterns that have communicative purposes. This study aims at investigating discourse patterns and its linguistic characteristics of applied linguistics article abstracts in English. The research corpus consisted of 30 research article abstracts in English written by English native speakers and published in Applied Linguistics journal and Journal of English for Academic Purposes in 2016-2018. The data were analyzed by using five-move abstract pattern proposed by Pho (2013). The results showed that the common patterns of the abstracts were the patterns which contained five moves and four moves. Furthermore, the abstracts tended to use present tense and active voice. It can be concluded the results provide new findings among study of discourse patterns of English research article abstracts written by English native speakers, especially in applied linguistics.